The inadequate protection for debenture holders in Nigeria. (2013)
This paper examined the legal protection for debenture holders in Nigeria. The debenture holders are investors and not shareholders and are subject to different regime of rights somehow different from that of shareholders. The legal title to the debenture stock is held by the Trustee to the debenture who is in turn appointed by the Company without any input by the debenture holders. The Trustee is the only recognized person to institute actions or realize the security in case of default, and where he fails in his duty the debenture holder is left at the mercy of the company. This paper considered all relevant legal options and current position of the law on how the debenture holders rights may be enforced and protected.